The ENRICH study to evaluate the effectiveness of a combination intervention package to improve isoniazid preventive therapy initiation, adherence and completion among people living with HIV in Ethiopia: Rationale and design of a mixed methods cluster randomized trial - Andrea A. Howard; Yael Hirsch-Moverman; Suzue Saito; Tsigereda Gadisa; Amrita Daftary; Zenebe Melaku (Contemporary Clinical Trials Communications, 2017)
Background: Isoniazid preventive therapy (IPT) prevents tuberculosis among HIV-positive individuals, however implementation is suboptimal. Implementation science studies are needed to identify interventions to address this evidence-to-program gap. Objective: The ENRICH Study is a mixed methods cluster randomized trial aimed at evaluating the effectiveness and acceptability of a combination intervention package (CIP) to improve IPT implementation in Ethiopia. Design: Ten health centers were randomized to receive the CIP or standard of care. The CIP includes: nurse training and mentorship using a clinical algorithm, tool to identify IPT-eligible family members, and data review at multidisciplinary team meetings; patient transport reimbursement; and adherence support using peer educators and interactive voice response messages. Routine data were abstracted for all newly-enrolled IPT-eligible HIV-positive patients; anticipated sample size was 1400 individuals. A measurement cohort of patients initiating IPT was recruited; target enrollment was 500 individuals, to be followed for the duration of IPT (6–9 months). Inclusion criteria were: HIV-positive; initiated IPT; age ≥18; Amharic-, Oromiffa-, Harari-, or Somali-speaking; and capable of informed consent. Three groups were recruited from CIP health centers for in-depth interviews: IPT initiators; IPT non-initiators; and health care providers. Primary outcomes are: IPT initiation; and IPT completion. Secondary outcomes include: retention; adherence; change in CD4+ count; adverse events; and acceptability. Follow-up is complete. Discussion: The ENRICH Study evaluates a CIP targeting barriers to IPT implementation. If the CIP is found effective and acceptable, this study has the potential to inform TB prevention strategies for HIV patients in resource-limited countries in sub-Saharan Africa.